Building climate resilience in the agriculture sector of Asia and the Pacific - International Food Policy Research Institute; Asian Development Bank (Asian Development Bank, 2009)
Climate change is threatening food production systems and therefore the livelihoods and food security of billions of people who depend on agriculture in the Asia and Pacific region (hereafter, Asia and the Pacific). Agriculture is the sector most vulnerable to climate change due to its high dependence on climate and weather and because people involved in agriculture tend to be poorer compared with urban residents. Consistent warming trends and more frequent and intense extreme weather events have been observed across Asia and the Pacific in recent decades. In line with these trends, climate change scenarios consistently project temperature increases across the region, which will require farmers to adapt to changing conditions. At the same time, agricultural activities release significant amounts of greenhouse gases (GHG) into the atmosphere. Asia and the Pacific accounts for 37% of the world’s total emissions from agricultural production, and the People’s Republic of China (PRC) alone accounts for more than 18% of the total.